Changes in Attitudes of the Young Generation in Persuasive Communication "Berani Hijrah" Community - Suci Wulan Dari; Zainun Zainun; Hasrat Efendi Samosir (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to change attitudes of the Young Generation in Persuasive Communication "Berani Hijrah" Community. This research on the Persuasive Communication Strategy of the Dare to Hijrah Community in Enhancing the Hijrah Spirit of the Young Generation was conducted at the Nurul Iman Mosque, Limau Manis Village, Tanjung Morawa. The location was chosen because this mosque is a public gathering and is used as a place for regular recitations by this community. The research method used is qualitative research, the most important sampling procedure is how to determine key informants or social situations that are full of information according to the research focus. The selection of resource persons in naturalist qualitative aims to optimize the scope and information needed. Resource persons are selected in the context of the research, through selected cases according to the focus and data needed to be analyzed. Informants in this study came from several categories. The process of attracting the attention of the younger generation in persuasive communication of the Berani Hijrah Community is the first by determining the goals and targets to be addressed, after that it will consider how the psychology of the young generation is at the exact target, which is like following the times that are trending among young people, after it included it in the theme of the study so that it easily attracted the attention of the younger generation to attend. Second, by inviting famous clerics who are going viral, this will have a huge impact on the wider community because it will be very easy to bring in the masses if they bring in people who are more famous. Third, use media that is widely used by the younger generation.